2000
DOI: 10.1021/la0010626
|View full text |Cite
|
Sign up to set email alerts
|

A Sponge Morphology in an Elementary Coacervate

Abstract: A zwitterionic gemini surfactant forms a coacervate which is "elementary" in the sense that it consists of a single solute as opposed to the multicomponents (e.g., cetylpyridinium chloride/hexanol/water/NaCl) common in the coacervate literature. The gemini dissolves in water but then quickly separates as oily droplets which, despite the high water content of 83 wt %, are immiscible with water. Cryogenic temperature high-resolution scanning electron microscopy (cryo-HRSEM) examination of the droplets shows a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 24 publications
3
84
0
4
Order By: Relevance
“…Two aqueous phases are immiscible for the liquid–liquid phase separation state. One is polymer rich phase and another is so‐called equilibrium liquid which is usually polymer poor phase . The polymer rich colloidally stable liquid droplets are called as a coacervate.…”
Section: Introductionmentioning
confidence: 99%
“…Two aqueous phases are immiscible for the liquid–liquid phase separation state. One is polymer rich phase and another is so‐called equilibrium liquid which is usually polymer poor phase . The polymer rich colloidally stable liquid droplets are called as a coacervate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a primitive selection could occur which would favor such coacervates. The coacervate systems have been studied also more recently (Burgess 1990;Burgess et al, 1991;Burgess and Singh 1993;Dubin et al, 2008;Liberatore et al, 2009;Menger 2002Menger , 2011Menger et al, 2000;Menger and Sykes, 1998;McClements et al, 2009;Rabiskova et al, 1994;Singh and Burgess, 1989;Stuart et al, 1998;Wang et al, 1999Wang et al, , 2000, but not in the prebiotic context.…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…In ''The Origin of Life'', [1] A. I. Oparin addressed the importance of coacervate droplets as the possible origin of living cells in the primitive sea. Hence, many researchers have focused on the properties of coacervate and its applications, [2][3][4][5][6][7][8][9][10] which have been extensively investigated in diverse fields such as polymer sciences, [7,8] food hydrocolloids [9] and life sciences. [10] Recently, we have found that the polyzwitterion poly [3-(N,N-dimethyl-N-metacryloyloxyammonium)propanesulfonic acid] (PDMAPS), [11][12][13] which has both positive and negative univalent charges on each side group along the polymer chain (Figure 1(a)), has an upper critical solution temperature (UCST) and forms coacervate droplets by itself on cooling.…”
Section: Introductionmentioning
confidence: 99%